Tn5supF, a 264-base-pair transposon derived from Tn5 for insertion mutagenesis and sequencing DNAs cloned in phage lambda. - Phadnis, S H (1989)
We constructed a derivative of transposon Tn5 called Tn5supF for insertion mutagenesis and sequencing DNAs cloned in phage lambda. This element carries a supF amber-suppressor tRNA gene. Its insertion into lambda can be selected by plaque formation by using nonsuppressing (sup0) Escherichia coli for amber mutant lambda phage and sup0 dnaB-amber E. coli for nonamber lambda phage. Tn5supF is just 264 base pairs long. It transposes efficiently and inserts quasi-randomly into DNA targets. The unique sequences near its termini can be used as primer binding sites for dideoxynucleotide DNA sequencing, thus permitting the direct sequencing of DNAs cloned in phage lambda without subcloning.